Do Foreign Owners Favor Short-Term Profit? Evidence from Germany - Verena Dill; Uwe Jirjahn; Stephen C. Smith (Universität Trier, Fachbereich IV – Volkswirtschaftslehre, 2013)
Comparing domestic- and foreign-owned firms in Germany, this paper finds that foreign-owned firms are more likely to focus on short-term profit. This influence is particularly strong if the local managers of the German subsidiary are not sent from the foreign parent company. Moreover, the physical distance between the foreign parent company and its German subsidiary increases the probability of focusing on short-term profit. These findings conform to the hypothesis that foreign owners facing an information disadvantage concerning the local conditions of their subsidiaries are more likely to favor short-term profit. However, we do not identify differences in short- termism between investors from Anglo-Saxon and other foreign countries; rather, results point in the direction of more general features of international business investment.
Keywords: F23; G34; M16; P10; 330; Foreign Ownership; Short-Termism; Asymmetric Information; Globalization